2019
DOI: 10.1108/jedt-02-2018-0033
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing environment sustainability enablers using fuzzy DEMATEL for an Indian steel manufacturing company

Abstract: Purpose The purpose of this paper is to analyze the Environmental Sustainability Enablers (ESEs) for an Indian steel manufacturing company to select the appropriate set of ESEs for implementing and enhancing environmental sustainability. Design/methodology/approach A methodology using fuzzy Decision-Making Trail and Evaluation Laboratory (DEMATEL) is proposed to analyze ESEs capturing multiple experts’ qualitative judgments on their mutual impacts. It is applied to an Indian steel manufacturing company to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 93 publications
0
22
0
Order By: Relevance
“…Fu and Geng (2019) indicated that regulatory compliance enhances green development associated with environmental sustainability practices. Goyal et al (2019) also revealed that environmental compliance certification is a significant environmental sustainability enabler.…”
Section: Regulatory Compliance and Environmental Sustainability Practicesmentioning
confidence: 99%
“…Fu and Geng (2019) indicated that regulatory compliance enhances green development associated with environmental sustainability practices. Goyal et al (2019) also revealed that environmental compliance certification is a significant environmental sustainability enabler.…”
Section: Regulatory Compliance and Environmental Sustainability Practicesmentioning
confidence: 99%
“…Kumar and Dash (2016) constructed influential network relation map of consumer decision-making in e-marketplace applied DEMATEL method. In relate with environment protection, Goyal et al (2019) analyzed environment sustainability enablers using fuzzy DEMATEL. Tsai et al (2015) used the Fuzzy DEMATEL to Determine Environmental Performance.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, inner dependency among the criteria can be handled in these studies. On the other side, Lo et al [78], Wang et al [79] and Goyal et al [80] considered fuzzy DEMATEL to weight the criteria for the selection of recycling partner, e-commerce performance and measuring environmental sustainability. With the help of fuzzy DEMATEL approach, impact relation map can be created in these studies.…”
Section: Literature Review On Fuzzy Multi-criteria Decision-making Mementioning
confidence: 99%